Wages in the Netherlands: a Micro Approach - Stefan Groot (European Regional Science Association (ERSA), 2010)
Many OECD countries have experienced growing wage inequality since the 1980s. This trend is generally explained by increasing relative demand for skilled labor due to skill biased technological progress and, to some extent, globalization. By using micro data from Statistics Netherlands, this paper examines trends in Dutch (real pre-tax) wage inequality between 2000 and 2005, thus extending the previous literature by covering recent years. We find that inequality, after correcting for observed worker characteristics, decreased somewhat at the lower half of the wage distribution, while increasing slightly at most of the upper half, and relatively strong at the highest few percentiles. Wage growth was also higher for occupation categories with a higher initial wage level, and for workers in the Randstad agglomerations. It is shown that changes in the wage structure are to a large extent explained by prices and quantities of worker characteristics, while changes in the residual wage distribution play a role at the highest percentiles.
Keywords: 330